2008
DOI: 10.1038/cmi.2008.58
|View full text |Cite
|
Sign up to set email alerts
|

The Abnormal High Expression of B Cell Activating Factor Belonging to TNF Superfamily (BAFF) and Its Potential Role in Kidney Transplant Recipients

Abstract: B cell activating factor belonging to TNF superfamily (BAFF) is a critical regulator of B cell maturation and survival. In this present study, the expression characteristic of BAFF in kidney transplantation recipients was investigated, its potential significance was analyzed and peripheral blood of follow-up kidney transplant recipients was studied. Flow cytometric assay results showed that, cell-surface BAFF was significantly highly expressed on peripheral CD3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(28 reference statements)
1
11
0
1
Order By: Relevance
“…The inflammatory cytokine IL6 supports long-lived plasma cell survival in vitro and it is increased in the serum of patients with SLE 14,50 and in monocytes from SLE patients. 51 Increased expression of the prosurvival cytokine BAFF has also been associated with abnormal renal function, 52 and in patients with active SLE, BAFF is expressed by CD4 and CD8 T cells but also by plasma cells from both the bone marrow and kidneys, 31,53 raising the possibility that autocrine secretion of BAFF might promote PC survival in lupus kidneys. Further characterization of the factors that regulate survival of these cells will be crucial to devise methods for their control.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokine IL6 supports long-lived plasma cell survival in vitro and it is increased in the serum of patients with SLE 14,50 and in monocytes from SLE patients. 51 Increased expression of the prosurvival cytokine BAFF has also been associated with abnormal renal function, 52 and in patients with active SLE, BAFF is expressed by CD4 and CD8 T cells but also by plasma cells from both the bone marrow and kidneys, 31,53 raising the possibility that autocrine secretion of BAFF might promote PC survival in lupus kidneys. Further characterization of the factors that regulate survival of these cells will be crucial to devise methods for their control.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF/BLyS and APRIL blockade prevents B cell maturation, differentiation, and survival [86]. Xu et al found a gradual increase in levels of BAFF over time in kidney transplant recipients as well as higher levels of BAFF expression on CD3 T cell in patients with poorer graft function [87]. BAFF has been shown to influence class switching of immunglobulins, enhance survival and effector function of plasmablasts [8890] as well as memory B cell differentiation into Ig-secreting cells in a T cell dependent manner, while opposite results were seen with respect to T cell independent responses [91].…”
Section: The Effects Of Immunosuppressants On B- Cellsmentioning
confidence: 99%
“…BAFF and APRIL are members of the TNF family and contribute to survival of bone marrow plasma cells. Recent studies have shown up-regulation of BAFF in peripheral blood of patients with AMR (3031). CD138+ plasma cells could still be associated with AMR that was missed in our study due to small sample size and inability to examine DSA, BAFF, or APRIL.…”
Section: Discussionmentioning
confidence: 99%